(untitled) (Journal of Technology and Operations Management, 2012)
Nowadays, many companies have been using their websites to share job opportunities with job seekers. This paper aims to provide further explanation about the customer interface satisfaction on the use of job search website in Malaysiausing technology acceptance model (TAM) and service quality (SERVQUAL) in the case of Universiti Utara Malaysia (UUM) students. Furthermore, the conceptual framework which the researcher attempts to operate in this study includes TAM, SERVQUAL and Customer Satisfaction. More than 100 surveys in both questionnaires and online surveys were distributed to UUM final year students who have used job search website. The result of this study revealed significant relationships between TAM, SERVQUAL and interface satisfactions of job search websites.